KEANEKARAGAMAN HERPETOFAUNA DI KAWASAN TAMBLING WILDLIFE NATURE CONSERVATION (TWNC) TAMAN NASIONAL BUKIT BARISAN SELATAN (TNBBS) PESISIR BARAT LAMPUNG - Bobi, Muhammad; Erianto, .; Rifanjani, Slamet (Universitas Tanjungpura, 2017)
Data was collected using VES (Visual Encounter Survey) methods in which we observed and recorded any species that had been seen. Methods VES (Visual Encounter Survey) was combined with transect sampling. We surveyed two transects, one located in aquatic and one in terrestrial habitats. This study aims to calculate the species diversity, species richness, relative abundance, and evenness index for this population. We found 22 species of amphibians and reptiles. This total contains 11 species (Frog and Toad) of Order Anura included in the families Bufonidae (3 genus), Dicroglossidae (1 species), Ranidae (4 genus), Rhacophoridae (1 genus), and Microhylidae (2 genus); and 11 species of Â Order Squamata included in the family Agamidae (2 genus), Gekkonidae (3 genus), Scincidae (2 genus), Varanidae (1 genus), and Colubridae (4 genus). We calculated that for this community, the diversity index was 1.04, the evenness index was 0.77, the richness index was 4.03, the abundance index was 0.044, the results and dominance index was 4.03, and the total number of individuals encountered was 183.Keywords: Amphibians and reptiles, Diversity, Visual Encounter Survey.